A search for pair-produced resonances in four-jet final states at $\sqrt{s} =$ 13 TeV with the ATLAS detector - ATLAS collaboration (2876 authors) (2018)
A search for massive coloured resonances which are pair-produced and decay into two jets is presented. The analysis uses 36.7 fb$^{-1}$ of $\sqrt{s}$ = 13 TeV pp collision data recorded by the ATLAS experiment at the LHC in 2015 and 2016. No significant deviation from the background prediction is observed. Results are interpreted in a SUSY simplified model where the lightest supersymmetric particle is the top squark, $\tilde{t}$ , which decays promptly into two quarks through R-parity-violating couplings. Top squarks with masses in the range $100~\text {GeV}<m_{\tilde{t}}<410$   $\text {GeV}$ are excluded at 95% confidence level. If the decay is into a b-quark and a light quark, a dedicated selection requiring two b-tags is used to exclude masses in the ranges $100~\text {GeV}<m_{\tilde{t}}<470$   $\text {GeV}$ and $480~\text {GeV}<m_{\tilde{t}}<610$   $\text {GeV}$ . Additional limits are set on the pair-production of massive colour-octet resonances.